Implementasi Kebijakan Perda Kabupaten Batu Bara No. 9 Tahun 2014 untuk Pengembangan Pariwisata Pantai Sejarah Berbasis Masyarakat dalam Meningkatkan Pendapatan Asli Daerah di Kabupaten Batu Bara - Faizal Faizal; Budi Hartono; Isnaini Isnaini (Mahesa Research Center, 2023)
The purpose of this writing is to analyze the implementation of Regional Regulation of Batu Bara District No. 9 of 2014 concerning the Master Plan for Regional Tourism Development for the period of 2014-2029 and the challenges faced in developing Community-Based Historical Beach Tourism to increase Local Revenue in Batu Bara District. This research used a descriptive method with a qualitative descriptive data analysis technique. Primary data was obtained through observation, interviews, and documentation. The results of the research showed that in terms of communication, resources, disposition, and bureaucratic structure, the implementation has been optimal. The challenges faced include limited financial resources and infrastructure, as well as the attitude of policy implementers which is not always positive towards the implementation of the policy. The implementation of Regional Regulation No. 9 of 2014 in Batu Bara District has a positive impact on local revenue, thereby increasing the Local Revenue.